Manajemen Pembiayaan Pendidikan Islam - Khafidhoh Khafidhoh; Aulia Kiftiah Kencana; Muhammad Alawilhuda (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
One of the areas worked on in school-based management is financing management. Good financing management is necessary because it is believed that with efficient and effective school financial management, errors, leakages, and variations in the use of funds from the original plan and goals will be avoided. Schools are empowered to assess their own needs through school-based financing management, which transfers control over budget allocation and use to schools. To completely reduce dependence on government funding, schools are also allowed to engage in income-generating activities. Financing management needs to be carried out carefully, diligently, and comply with relevant regulations when implementing school-based management. The preparation of school revenue and expenditure budget plans (RAPBS) as well as various forms and sources of school funding are all included in the idea of school-based financing management.